INTEGRATION OF MEDICARE AND MEDICAID: RESULTS OF CALIFORNIA'S DUAL FINANCIAL ALIGNMENT DEMONSTRATION. (11th November 2018) - Graham, C; Liu, P; Kaye, S
Abstract: In 2014, California became one of 14 states to implement a dual financial alignment demonstration. A capitated managed care model was used to transition almost 120, 000 seniors and people with disabilities into managed care plans called "Cal MediConnect" (CMC). Though all dually eligibles in demonstration counties were initially transitioned into the program, almost half opted out. Those who remained in the program had all of their medical care and long-term services and supports managed by one health plan. A key feature of the program was the development of care coordination through the plan. Researchers at the University of California conducted a longitudinal survey (n=2, 100) examining enrollees experiences with access to care, coordination of care, and quality of care compared to: 1) those who opted out, and 2) a sample of duals in non-demonstration counties. Beneficiaries participated in a survey in 2016 and then a follow up survey in 2017. Results show that CMC beneficiaries rate their satisfaction with benefits and quality of care very favorably and there was a reduction in ED use. Those with more functional impairment/higher LTSS needs had lower satisfaction and more unmet needs, especially in the area of assistive equipment. Those in the CMC plan had an overall increase in Medi-Cal personal care service hours, and fewer unmet needs for personal care compared to those in non-demonstration counties. This paper will discuss the overall success of the programs, lessons learned, and challenges that still remain in integrating Medicare and Medicaid, especially when LTSS is integrated.